1989
DOI: 10.1126/science.2683073
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Pertussis Toxin Suitable for Vaccine Development

Abstract: Immunization with chemically detoxified pertussis toxin can prevent severe whooping cough with an efficacy similar to that of the cellular pertussis vaccine, which normally gives unwanted side effects. To avoid the reversion to toxicity and the loss of immunogenicity that may follow chemical treatment of pertussis toxin, inactive toxins were constructed by genetic manipulation. A number of genetically engineered alleles of the pertussis toxin genes, constructed by replacing either one or two key amino acids wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
0
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(209 citation statements)
references
References 27 publications
8
197
0
4
Order By: Relevance
“…The ADP-ribosyltransferase activity of the recombinant S1 (rPTS1) encoded by pTrcHis2/pts1 and pcDNA3.1/ptS1 was inactivated by two point mutations in which Arg-13 was changed to Leu-13 and Glu-129 was changed to Gly-129 (Pizza et al, 1989). Site-directed mutagenesis was carried out using a QuikChange XL mutagenesis kit (Stratagene) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ADP-ribosyltransferase activity of the recombinant S1 (rPTS1) encoded by pTrcHis2/pts1 and pcDNA3.1/ptS1 was inactivated by two point mutations in which Arg-13 was changed to Leu-13 and Glu-129 was changed to Gly-129 (Pizza et al, 1989). Site-directed mutagenesis was carried out using a QuikChange XL mutagenesis kit (Stratagene) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an important aspect in the development of our DNA vaccine was the inactivation of the S1 gene. Pizza et al (1989) showed that substitution of Glu-129 with Gly-129 in combination with either Arg-9 to Lys-9, Arg-13 to Leu-13 or Trp-26 to Ile-26 abolished the ADP-ribosylase activity but did not adversely affect immunogenicity. Nencioni et al (1990) later characterized the 9K/129G toxoid and showed that it had the same physical and immunological properties as wild-type PT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chemical treatment lowers to some extent immunogenicity of PT. In contrast, genetically detoxified PT mutants -including PT-9K/129G, that lacks enzymatic activity -retain the functional and immunological properties of wild-type PT [9]. PT-9K/129G was shown to be safe and immunogenic as a component of a DTaP vaccine evaluated in two large Phase III efficacy trial in infants [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…But this time he and colleague Mariagrazia Pizza used sitedirected mutagenesis to specifically alter amino acids in the active site of the toxin. The result was a nontoxic molecule that made a potent vaccine (4).…”
Section: New Generation Of Vaccinesmentioning
confidence: 99%